Occupational Safety in Production of Traditional Fishing Vessels in Indonesia - Koto, Jaswar; Arief, Dodi Sofyan; Munirah, M. (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2014)
Traditional ship in Indonesia which usually built from wood has small capacity compared to modern steel ship. Compared to modern ship building, mostly the production is to assemble block by block with machines and big cranes. However, traditional ship is one hundred per cent made from the work of man. Workers are not properly trained in a formal engineering school but only learnt the skill from senior workers. Hence, all modern concepts such as the need for safety and a proper ship production flow are not a great concern for them. In this paper, safety issue in traditional ship production process is being observed conducting direct survey to traditional shipbuilding company in Bintan, Indonesia. It is hoped that the outcome is to bring safety awareness to the traditional ship builders.